Pore structure characteristics of reservoirs of Xihu Sag in East China Sea Shelf Basin based on dual resolution X-ray computed tomography and their influence on permeability. (15th January 2022) - Zeng, Fang; Dong, Chunmei; Lin, Chengyan; Tian, Shansi; Wu, Yuqi; Lin, Jianli; Liu, Binbin; Zhang, Xianguo
Abstract: To investigate the effects of differences in resolution on the analysis of pore structures, and the significance of the high-resolution imaging and the upscaling of the pores from small-scale to large-scale, five cylindrical core plugs with a range of permeabilities were selected and sub-plugs drilled from each of them. Both sets of samples were then scanned by X-ray microscope computer tomography imaging technology (XCT), and mercury intrusion porosimetry (MIP) experiments were conducted on the core plugs. The relationships between pore structure parameters of dual resolutions and the permeability show that the coordination number, connectivity based on the low-resolution XCT data, and pore throat radius, based on the high-resolution XCT data, are the main parameters controlling the permeability. In addition, four zones of pore-throats (radii are >25 μm, 5–25 μm, 0.5–5 μm, and <0.5 μm) and the contributions to permeability were determined based on the MIP data. The results indicate that the smaller throats (<5 μm) contribute differently to permeability (0 to sample 1 and 100% to sample 5). When these throats contribute much to permeability, the studies of high-resolution XCT and upscaling are significant. Meanwhile, these studies can be ignored when they contribute little to permeability. Graphical abstract: Image 1 Highlights: X-ray Computed Tomography (XCT) is a key study technology of pore structures. Coordination numbers and connectivity of low resolutions XCT affect permeability. Throat radii of high resolutions XCT affect permeability. Tortuosity affects permeability obviously when pore- and throat-radii are similar. Significance of upscaling depends on contributions of small-throat to permeability.